YOUTH NUTRITION EDUCATION FOR FEMALE STUDENTS - Dewi Andariya Ningsih; Eliyawati; Istidamatul Ludvia; Lutfiatur Rohmani; Ganis Yunita Prativie; Yeni kurniawati; Dewi Qurrotul A’yun; Siti Romlah; Tiara Indriani; Susiana; Umi Nur Kholifah; Silaturrohmih; Siti Hilmi Musyarrofah; Siti Nurhidayati (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2022)
Adolescence is characterized by a phase of rapid growth and development in which the need for nutrients and micronutrients is relatively high. Adolescents with good nutritional knowledge are more likely to follow healthy eating habits. In this regard, this community service is planned to assess basic knowledge related to nutrition for adolescent girls in increasing their knowledge related to nutrition. Main Activities Educational activities on adolescent nutrition, the target is young female students of the Salafiyah Syafi'iyah Sukorejo Islamic Boarding School, located on the Faculty of Health Sciences Campus. The purpose of the implementation is to increase the insight of young women about balanced nutrition in adolescents . The conclusion of this activity is that most of the young female students have not implemented a healthy lifestyle in their daily life, most of the nutritional status of the female students are normal nutrition, most of the teenage students